The EEG in Huntington's chorea: a clinical and neuropathological study - Scott, D. F. (1972)
The EEGs are reported on a group of 95 patients with Huntington's chorea. Thirty one showed little activity of any kind, and in particular no alpha rhythm above 10 μV in amplitude was seen. Only those records which still met these criteria when re-examined were included in the `low voltage' category. EEGs in this category occurred significantly more frequently in institutionalized patients and in those with a positive family history of Huntington's chorea, dementia, and choreiform movements together. Computer averaged responses to light and sound were found in the three patients examined, though their routine EEGs were low voltage. Neuropathological examination confirmed a clinical diagnosis of Huntington's chorea in 14 patients investigated. There was a statistically significant association between cortical atrophy, including the frontal lobe, and a `low voltage' EEG. It was concluded that the low voltage record, though not specific for Huntington's chorea, was rare in other neurological disorders. The EEG is therefore of value in patients suspected of having Huntington's chorea as well as in various presenile dementias.